PENGARUH EKSPEKTASI, PERSEPSI KUALITAS, PERSEPSI NILAI DAN CITRA TUJUAN WISATA TERHADAP KEPUASAN WISATAWAN PADA PULAU WEH SABANG - Amirul Azhar; Iskandarsyah Iskandarsyah (Departemen Manajemen, 2019)
Abstract: This study aims to measure the influence of expectations, perceived quality, perceived value and destination image on tourist satisfaction at Weh Island of Sabang. The sample used in this study is tourist visiting Weh Island of Sabang totaling 100 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Nonprobability Sampling. Multiple regression analysis was used as a method of analysis to determine the effect of all the variables involved. Based on the result analysis, indicating that expectation and destination image have an effect on tourist satisfaction. While, perceived quality and value do not havenot an effect on tourist satisfaction, Keywords: Expectations, Perceived Quality, Perceived Value, Destination Image, Tourist Satisfaction